HUBUNGAN KECERDASAN EMOSIONAL DENGAN PRESTASI MAHASISWA PRODI D III KEBIDANAN CURUP POLTEKKES KEMENKES BENGKULU - Sipahutar, Lydia Febrina (Politeknik Kesehatan Kemenkes Bengkulu, 2016)
During this time many people were found to achieve the required high learningachievement intellectual intelligence (IQ) is also high. However, EQ good can determine thesuccess of individuals in learning achievement in building a successful career, and can reducethe aggressiveness, especially among teenagers purpose of this study was to determinewhether there is a relationship of emotional intelligence toward student learning achievementProdi DIII Midwifery Curup Semester II and IV. This research was conducted in the ProdiDIII Midwifery Curup from July to August 2016, with the number of respondents, thisresearch is descriptive analytic, data collection using a scale based on the theory of emotionalintelligence Daniel Goleman; to measure student achievement used methods of examinationof documents by the second half saw the value of IP, IV and population II and IV semesterstudent, taken by total population, the data was analyzed by univariate and bivariate. Theresults of the analysis of experimental data showed correlation coefficient of 0.635 with p0.005 (<0.05), the Ha accepted. This means that there is a significant relationship betweenemotional intelligence and academic achievement of students Prodi DIII Midwifery Curup IIand IV semester of 2016. To develop and optimize the emotional intelligence plays a role instudent success both in school and in the surrounding environment, it is recommended to thecampus, especially the lecturer-dosenagar incorporate elements emosioal intelligence inpresenting the material as well as the emotions involved in the learning process